The 1994 English Curriculum of Secondary Schools and Its Implications to rhe Teaching of English in Indonesia - Ali Saukah (Universitas Negeri Malang, 2016)
The 1994 English curriculum has been implemented since the 1994-1995 academic year at the secondary schools. In order to implement the curriculum well, teachers and others concerned should understand the principles underlying the development of the curriculum. Implications of implementing the curriculum should also be considered very carefully so that optimal results can be expected. Four areas of implications will be discussed in this article, namely: teaching and learning activities, the training of English teachers, the teachers' lesson plans, and the evaluation procedures. In addition, two of potential problems of implementation will also be discussed